2001
DOI: 10.1002/1097-0142(20011015)92:8<2072::aid-cncr1547>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum amyloid a on the prognosis in patients with renal cell carcinoma

Abstract: BACKGROUND Evidence of systemic inflammation, i.e., elevation of serum C–reactive protein, interleukin‐6, and/or the erythrocyte sedimentation rate, is correlated to poorer prognosis of patients with renal cell carcinoma (RCC). Serum amyloid A (SAA) has been recognized mainly as acute‐phase reactant. METHODS Serum SAA from 72 patients with RCC were examined. Thirty‐eight of 72 patients with RCC had elevated SAA compared with 17 healthy donors. RESULTS The disease specific survival rate was significantly lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 9 publications
0
49
1
1
Order By: Relevance
“…In chronic inflammation, however, which plays a critical role in tumor development, SAA levels increase substantially and indeed also increase in a number of neoplastic diseases. It has been observed in previous studies that the SAA level increases in patients with stomach, lung, renal, colorectal, breast and other forms of cancers (Biran et al, 1986;Glojnaric et al, 2001;Kimura et al, 2001;O'Hanlon et al, 2002;Cho et al, 2004;Chan et al, 2007;Farooqui et al, 2012). With regard to HCC, only one research confirmed the relation of circulating SAA with HCC, and verified a gradual increase of SAA levels in serum from normal to HBV and then to HCC, but cannot be regarded as a specific indicator for assessing HBV and HCC.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In chronic inflammation, however, which plays a critical role in tumor development, SAA levels increase substantially and indeed also increase in a number of neoplastic diseases. It has been observed in previous studies that the SAA level increases in patients with stomach, lung, renal, colorectal, breast and other forms of cancers (Biran et al, 1986;Glojnaric et al, 2001;Kimura et al, 2001;O'Hanlon et al, 2002;Cho et al, 2004;Chan et al, 2007;Farooqui et al, 2012). With regard to HCC, only one research confirmed the relation of circulating SAA with HCC, and verified a gradual increase of SAA levels in serum from normal to HBV and then to HCC, but cannot be regarded as a specific indicator for assessing HBV and HCC.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, recent epidemiologic studies even suggest that elevated circulating levels of SAA, not only merely mark the presence of prevalent carcinoma, but also should possibly be related to an increased risk of future cancer in apparently healthy individuals (Sasazuki et al, 2010;Shiels et al, 2013). Most importantly, several researches have confirmed that SAA turned out to be an independent and effective factor in predicting survival of patients with different tumors (Kimura et al, 2001;Chan et al, 2007;Meng et al, 2014).…”
Section: Serum Amyloid a Is A Novel Prognostic Biomarker In Hepatocelmentioning
confidence: 96%
See 1 more Smart Citation
“…HP is a well characterized APP with increasing evidence as a cancer biomarker [21][22][23][24][25]. Lastly, SAA is an acute phase apolipoprotein associated as a marker of cancer progression [26][27][28][29][30]. In NB, Combaret et al identified high SAA levels were detected in patient sera with poor prognosis [31].…”
Section: Resultsmentioning
confidence: 99%
“…Although our microarrray experiments identified significantly increased expression of IL-8 in aggressive primary and metastatic CCRCC, this differential expression was marginally significant (P < 0.055) by our quantitative RT-PCR experiments. Another gene, serum amyloid A, has been identified in the serum of CCRCC patients, and elevated serum levels are associated with aggressive CCRCC (25). Serum amyloid A1 and A2 are acute-phase reactants whose expression is regulated in part by IL-1 and IL-6 (26 -28).…”
Section: Discussionmentioning
confidence: 99%